The Utility of the Bering Sea and East Asia Rules in Long-Range Forecasting - Joseph S. Renken; Joshua J. Herman; Travis R. Bradshaw; Patrick S. Market; Anthony R. Lupo (Advances in Meteorology)
Using the National Center for Atmospheric Research/National Centers for Environmental Prediction (NCAR/NCEP) reanalyses and the daily Pacific North American (PNA) index values from the Climate Prediction Center from 1 January 1950 to 31 December 2016, the utility of the Bering Sea Rule (BSR) and the East Asia Rule (EAR) for making forecasts in the two-to-four-week time frame for the central USA region is examined. It is demonstrated using autocorrelation and Fourier transforms that there may be a degree of predictability in this time frame using the PNA, another teleconnection index, or some variation of them. Neither the BSR nor EAR based forecasts showed skill over climatology in the traditional sense, but using signal detection techniques these indexes were skillful at predicting the onset of anomalous temperature conditions (greater than two standard deviations) in the central USA. The BSR generally produced better results that the EAR and formulae for each index are proposed. Three case studies demonstrate the efficacy of these indexes for forecasting temperatures in the central USA. Then, it is proposed that the success of these indexes is likely due to a strong, quasistationary, and persistent Rossby wave train in the Pacific teleconnection region.